Development of a rhythmic gymnastics model to improve motor skills of students with mild special needs - Agung Nugroho; Andri Arif Kustiawan; Nazwa Amalia (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study aims to develop rhythmic gymnastics learning model to improve gross motor skills of students with mild intellectual disabilities in special schools. The research employed a research and development (R&D) approach adapted from systematic development stages, including needs analysis, model design, expert validation, limited trials, revisions, and effectiveness testing. The subjects were 40 students with mild intellectual disabilities from special schools in Medan selected through purposive sampling. Data were collected using expert validation sheets, questionnaires, and gross motor skill tests administered through pretest and posttest. Quantitative data were analyzed using paired sample t-tests. The results showed a significant improvement in students’ gross motor skills after implementation of the model (p < 0.05). The model, characterized by simple, repetitive movements integrated with music, was found to be feasible, practical, and effective for supporting adaptive physical education learning.